2022
DOI: 10.3390/cancers14020350
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Response to Immunotherapy in Non-Small Cell Lung Cancer Using Delta-Radiomics

Abstract: Delta-radiomics is a branch of radiomics in which features are confronted after time or after introducing an external factor (such as treatment with chemotherapy or radiotherapy) to extrapolate prognostic data or to monitor a certain condition. Immune checkpoint inhibitors (ICIs) are currently revolutionizing the treatment of non-small cell lung cancer (NSCLC); however, there are still many issues in defining the response to therapy. Contrast-enhanced CT scans of 33 NSCLC patients treated with ICIs were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Combined with clinicopathological information, they successfully predicted the patients who would benefit from ICI treatment (the AUCs of the training and validation groups were 0.848 and 0.795, respectively). Similarly, Barabino et al (37) extracted the radiomics features of lung lesions from CT scans at baseline and the first evaluation and calculated their changes by absolute difference and relative reduction (Delta, D). After feature screening and model construction, 27 delta features were identified, which were able to distinguish the response to NSCLC immunotherapy with statistically significant accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with clinicopathological information, they successfully predicted the patients who would benefit from ICI treatment (the AUCs of the training and validation groups were 0.848 and 0.795, respectively). Similarly, Barabino et al (37) extracted the radiomics features of lung lesions from CT scans at baseline and the first evaluation and calculated their changes by absolute difference and relative reduction (Delta, D). After feature screening and model construction, 27 delta features were identified, which were able to distinguish the response to NSCLC immunotherapy with statistically significant accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Barabino et al. ( 37 ) extracted the radiomics features of lung lesions from CT scans at baseline and the first evaluation and calculated their changes by absolute difference and relative reduction (Delta, Δ). After feature screening and model construction, 27 delta features were identified, which were able to distinguish the response to NSCLC immunotherapy with statistically significant accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Liu et al [18] showed that relative variations in CT texture following treatment have the potential to assess the pathologic response to chemotherapy in patients with CRLMs and may be stronger indicators of response than changes in lesion size or volume. E. Barabino et al [19] showed that Delta-radiomic characteristics have the ability to overcome the limitations of iRECIST in immunotherapy and, potentially, quantify treatment response and predict treatment course. Lin X et al [20]found that the CT radiomics features were signi cantly changed in both the response group and the nonresponse group after two cycles of chemotherapy, and Post-chemotherapy radiomics features, delta features were helpful to evaluate the early chemotherapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…An AUC of 0.81 with radiomics alone jumped to 0.89 with the addition of MGMT values. In a study of patients with NSCLC treated with immune checkpoint inhibitors, Barabino et al 99 measured the changes in radiomic features and identified a set of nine textural features that differentiated PsP from true progression. They also observed that these features were different from those that distinguished patients who responded to therapy from those who experience progression.…”
Section: Using Radiomics To Predict and Distinguish Typical And Atypi...mentioning
confidence: 99%